Особенности управления строительным процессом в условиях глобализации - Камолов, Л.А.; Халмаматова, Л.А.; Калкоразов, Т.Т. (SCIENCE and SOCIETY, 2020)
The article defines the effective use of resources which are key factors to success, and with everyday growing competition, the guarantor of the survival of the construction of organization.
Keywords: management; building complex; building; conditions of globalization